Pattern of Vitamin D Status in Patients with Non-Specific Bone Pains- A Single Centre Study - Muhammad Shahzad Anwer; Mohsin Hussain; Jehanzeb Ur Rehman; Mehwish Gilani; Syed Mohsin Manzoor; Asif Ali (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the pattern of Vitamin D status in patients presenting with complaints of non-specific bone pains and to correlate the association of sunlight exposure with Vitamin D deficiency/insufficiencyStudy Design: Cross-sectional study.Place and Duration of Study: Department of Chemical Pathology, CMH, Abbottabad Pakistan, from Aug 2020 to Jul 2021.Methodology: All patients with non-specific bone pain were asked about demographic, clinical and sunlight exposure. Vitamin D assays were performed after history taking.Result: A total of 247 patients were tested for vitamin D levels. 103(41.7%) were male and 144(58.3 %) were females. 56(22.7%) had >60 minutes of daily sunlight exposure, 67(27.1%) had 30 to 60 minutes, and 124(50.2%) had less than 30 minutes of daily sunlight exposure. Vitamin D deficiency was found in 132(53.4%) patients, insufficiency was seen in 74(30.0%) patients and 41(16.6%) patients had normal vitamin D levels. Vitamin D deficiency correlated significantly with low sunlight exposure time.Conclusion: Vitamin D deficiency was seen in 53.4% of patients with non-specific bone pains, while insufficiency was seen in 30.0% of patients. Moreover, our study showed association of Vitamin D deficiency with a decreased duration of sunlight exposure.